Delay Tolerant Networks: Protocols and Applications - Vasilakos, Athanasios; Zhang, Yan; Spyropoulos, Thrasyvoulos V. (Wireless networks and mobile communications series, 2016)
Delay Tolerant Networks (DTN)- which include terrestrial mobile networks, exotic media networks, ad-hoc networks, and sensor networks- are becoming more important and may not be well served by the current end-to-end TCP/IP model. This book provides a self-contained, one-stop reference for researchers and practitioners who are looking toward the future of networking. The text presents a systematic exploration of DTN concepts, architectures, protocols, enabling technologies, and applications. It also discusses various challenges associated with DTN. The author includes a wealth of illustrative material written in an accessible tone for easy understanding of the topics covered in the book.